Phytochemical Analysis of Anacamptis Sancta: Glucomannan, Phenolic Components, and Antioxidant Activity - Aytar, Erdi can; Palaz, Esra bulunuz; Ozdemir, Alaaddin; Akinci, Irfan ersin; Kompe, Yasemin Ozdener (Periodicum Biologorum, 2024)
Background and purpose: This study investigated the extracts obtained from both the roots and above-ground parts ofAnacamptis sancta. A. sancta, an orchid species traditionally used for its potential health benefits due to its rich phytochemical composition, was the focus. The primary aim of this research was to analyze the phytochemical components ofA. sancta extracts and evaluate their antioxidant potential. By conducting comprehensive phytochemical analyses and assessing antioxidant activities, this study seeks to provide a deeper understanding of the medicinal properties ofA. sancta and contribute to its applications in functional foods andphar- maceuticals. Materials and methods: In this study, extracts derived from both the tubers and above-groundparts ofA. sancta were investigated. Plant samples were collected from the OndokuzMay & imath;s University Botanical Garden. Fourier transform infrared spectroscopy (FTIR) analysis was conducted using a Perkin Elmer Spectrum 400 spectrophotometer. Glucomannan content was measured calorimetrically using the Megazyme K-GLUM 03/20 analysis kit and UV-visible spectrophotometer. Analysis ofsecondary metabolites in the above-groundparts included determination oftotalphenolic, flavonoid, flavanol, tannin, and proanthocyanidin contents using Folin-Ciocalteu, AlCl3, and other appropriate methods. Antioxidant capacity was assessed through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, and compound identification in the above-ground parts was performed using gas chromatography/mass spectrometry (GC-MS) analysis. Results: In the tubers, aglucomannan content of 17.93% was detected, and FTIR analyses revealed the characteristic peaks ofglucomannan. The extracts demonstrated high antioxidant potential, with total phenolic content measured at 120.61 mg GAE/g extract, total flavonoid content at 295.46 mg QE/g extract, flavanol content at 32.30 mg QE/g extract, total tannin content at 3.05 mg GAE/g extract, and total proanthocyanidin content at 119.43 mg CAE/g extract. The IC50 value for DPPH radical scavenging activity was calculated to be 47.79 mg/mL. GC-MS analysis of the above-ground parts of the plant identified the presence of significant bioactive compounds, including hydroxyacetic acid, hydrazide (42.52%), propane, 1,1-dipropoxy- (16.94%), and 1,3-dioxolane-4-methanol, 2-ethyl (12.86%). In summary, this study presents a comprehensive analysis of the phytochemical profile ofA. sancta. Conclusions: Thefindingshighlight its significantglucomannancontent in tubers and strong antioxidant activity. Additionally, bioactive com pounds were identified in the above-ground parts. This research provides valuable insights into potential medicinal and industrial applications ofA. sancta.
Keywords: FTIR Analysis; GC-MS; Glucomannan; Phytochemical Profile; Terrestrial Orchid